Relevance of Islamic Religious Education Curriculum to Socio-Cultural Dynamics in Indonesia - Lintang Alifia Lbs; Juliani; Farlentia Era Dewi; Khairani Balqis; Dara Putri Cia (Journal of Contemporary Gender and Child Studies, 2024)
This study aims to analyze the relevance of the Islamic Religious Education (PAI) curriculum to the socio-cultural dynamics developing in Indonesia. The PAI curriculum has a strategic role in shaping the character and morals of students, so it must be able to respond to social changes, culture, and religious values in society. This study used a qualitative approach with document analysis methods and in-depth interviews with education stakeholders, such as teachers, students, and education experts. The results showed that the PAI curriculum in Indonesia has tried to keep up with socio-cultural developments, but there are still some challenges in its implementation. These challenges include the gap between teaching materials and community needs, lack of teacher training in dealing with contemporary issues, and resistance to curriculum innovation. This study suggests the need to strengthen the integration of local and global values in the PAI curriculum, the active involvement of the community in curriculum formulation, and the improvement of teacher competence to be able to teach PAI contextually and relevant to Indonesia's socio-cultural conditions. Thus, PAI curriculum can be more adaptive and contributive in facing the challenges of globalization and multiculturalism.